2010
DOI: 10.1111/j.1751-2980.2010.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of inflammatory bowel disease in China

Abstract: The epidemiology and phenotype of inflammatory bowel disease (IBD) in the Chinese population is not well-known. We performed a comprehensive search of the Chinese biomedical literature database from 1989 to 2007 using the following key words: inflammatory bowel disease (IBD), ulcerative colitis (UC), Crohn's disease (CD). The investigation of hospitalized IBD patients from 1990 to 2003 was also carried out in 23 medical centers of 11 cities over China. There are some notable epidemiological and phenotypical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 18 publications
2
52
0
1
Order By: Relevance
“…A recent report reviewed what is known about the epidemiology of IBD in China [7]. The authors reviewed the Chinese medical literature and found that in the years 1989-2003, there were reports totaling 143,511 patients with IBD, although it is uncertain if reports were mutually exclusive such that subjects would not have been counted more than once.…”
Section: Introductionmentioning
confidence: 98%
“…A recent report reviewed what is known about the epidemiology of IBD in China [7]. The authors reviewed the Chinese medical literature and found that in the years 1989-2003, there were reports totaling 143,511 patients with IBD, although it is uncertain if reports were mutually exclusive such that subjects would not have been counted more than once.…”
Section: Introductionmentioning
confidence: 98%
“…This disease is chronic, incurable, and prone to relapse. As lifestyles continue to move toward a more Western style, the incidence and prevalence of CD in China have been increasing [1,2] , and as a result, this disease continues to attract the attention of researchers and clinical physicians. Approximately 75%-80% of patients require surgical resection at some point in their lives after a diagnosis of CD [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting this trend, in a comparative study, the UC:CD ratio was approximately 2.0 in Asia and 0.5 in Australia [1]. Various studies across Asia have shown that the UC:CD ratio is narrowing [7,8]. Although there is increased disease awareness, access to medical care and improved diagnostic tools may play a role in this epidemiological shift [9]; these factors alone are unlikely to account for the entirety of such changes.…”
Section: Epidemiologymentioning
confidence: 99%